Driving and Engine Cycles - Giakoumis, Evangelos G.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book presents in detail the most important driving and engine cycles used for the certification and testing of new vehicles and engines around the world. It covers chassis and engine-dynamometer cycles for passenger cars, light-duty vans, heavy-duty engines, non-road engines and motorcycles, offering detailed historical information and critical review. The book also provides detailed examples from SI and diesel engines and vehicles operating during various cycles, with a focus on how the engine behaves during transients and how this is reflected in emitted pollutants, CO2 and after-treatment systems operation. It describes the measurement methods for the testing of new vehicles and essential information on the procedure for creating a driving cycle. Lastly, it presents detailed technical specifications on the most important chassis-dynamometer cycles around the world, together with a direct comparison of those cycles.
Introduction -- Light-Duty Vehicles -- Motorcycles -- Heavy-Duty Vehicles and Engines -- Non-Road Engines -- Driving Cycles Test Procedure -- Appendix.
Keywords: Mechanical engineering; Mechanical Engineering